THE LOW ESTABLISHMENT OF THE PPAT WORKING HONORARIUM ON THE TRANSFER OF LAND RIGHTS IN JAYAPURA CITY FROM A SHARIA ECONOMIC PERSPECTIVE - MUHAMAD ZAINAL ABIDIN; MUHAMMAD ABDUL AZIZ (Islamic Economic and Business Journal, 2022)
There are 24 Land Deed Officials (PPAT) in the city of Jayapura. In the Government Regulation of the Republic of Indonesia number 24 of 2016 regarding Land Deed Making Officials (PPAT), in article 32 paragraph 1 regarding honoraria, rules have been set regarding honoraria for PPAT officials, but in reality there are many land deed making officials who handle the transfer of land rights under 1% of the regulations of the government of the republic of Indonesia. The purpose of this research is to find out the factors that influence differences in the awarding of honoraria for land deed officials (PPAT) in Jayapura City. In addition, from the standpoint of Sharia economic law, solutions to the low application of honoraria are sought. The research method uses descriptive qualitative research with a normative juridical approach. The results of the study show that the factors that influence differences in the awarding of PPAT work honoraria in Jayapura City are the low relationships between PPATs. There is a perception of freedom to grant honoraria that do not exceed 1%, and there is no stipulation for honoraria below 1%.